2020
DOI: 10.1108/ijrdm-09-2019-0291
|View full text |Cite
|
Sign up to set email alerts
|

Digimums' online grocery shopping: the end of children's influence?

Abstract: PurposeThis paper investigates children's influence on their mothers' online grocery shopping. As virtual shopping does not provide instant gratification, the authors explore how children between the ages of 7 and 11 are involved in the online purchasing process (before, during and after the purchase) with their digital mothers (digimums).Design/methodology/approachWe collected qualitative data from 27 separate semi-structured interviews of mothers and their children.FindingsChildren's influence during the onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Despite “Consumer Socialization and Intergenerational Influence” being the largest perspective, only four studies have addressed the Internet's role (Ayadi & Muratore, 2020; Ghouse et al, 2020; Kowalczyk & Royne, 2016; Niu, 2017). Considering the Internet's potential to impact key consumer socialization areas—like advertising knowledge, transaction understanding, and decision‐making skills—identified by John (1999), there is a significant gap opportunity for research.…”
Section: Agenda For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite “Consumer Socialization and Intergenerational Influence” being the largest perspective, only four studies have addressed the Internet's role (Ayadi & Muratore, 2020; Ghouse et al, 2020; Kowalczyk & Royne, 2016; Niu, 2017). Considering the Internet's potential to impact key consumer socialization areas—like advertising knowledge, transaction understanding, and decision‐making skills—identified by John (1999), there is a significant gap opportunity for research.…”
Section: Agenda For Future Researchmentioning
confidence: 99%
“…The publications in this perspective are part of an academic trend that, especially since the 2000s, have posited that children's influence over purchasing decisions has grown significantly, and that decision‐making within families has become increasingly collaborative (Sharma & Sonwaney, 2014). These studies address, for example, children's influence over parents concerning the selection of family dining‐out options (Chen et al, 2016), over their mothers' online grocery shopping (Ayadi & Muratore, 2020), or supermarket shopping behavior (Page et al, 2018).…”
Section: Framework‐based Reviewmentioning
confidence: 99%
“…Similarly, a North American survey among online grocery shoppers found that participants wished that there were the same store circulars and in-store sales in online grocery platforms [71]. Though limited, promotional tactics included price promotions such as discounting [92] and buy-one-get-one [39]. These promotions changed weekly (as is typical in North America) or up to every eight weeks (as is more typical in Europe) [56].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, 70% of all French people consider themselves to be ecoresponsible. Given the influence of children on food shopping in the family setting (Ayadi & Muratore, 2020), this context might arouse children's awareness about the origins of food, and the related natural and environmental issues (including agricultural practices, and the naturalness of the products). To explore children's engagement with environmental issues, we took a child-centric approach (Banister & Booth, 2005).…”
Section: Methodsmentioning
confidence: 99%